Safranal Alleviated OVA-Induced Asthma Model and Inhibits Mast Cell Activation - Lertnimitphun, Peeraphong; Zhang, Wenhui; Fu, Wenwei; Yang, Baican; Zheng, Changwu; Yuan, Man; Zhou, Hua; Zhang, Xue; Pei, Weizhong; Lu, Yue; Xu, Hongxi (Frontiers in Immunology, 2021)
Introduction: Mast cells are related to many allergic diseases, including asthma, systemic anaphylaxis, etc. Many compounds derived from Chinese herbal medicine have promising effects on stabilizing mast cells and decreasing inflammatory mediator production. Safranal, one of the active compounds from Crocus sativus, shows many anti-inflammatory properties. In this study, we investigate the effectiveness of safranal on stabilizing mast cell degranulation and inhibiting the production of inflammatory mediators. Furthermore, we investigated this effect in vivo via the passive systemic anaphylaxis (PSA) model and evaluated the effect of safranal on ovalbumin (OVA)-induced asthma in mice. Methods: OVA-induced asthma and PSA model were used to evaluate the effect of safranal in vivo. Lung tissues were collected for H&E, TB, IHC and PAS staining. ELISA were used to determine level of IgE and chemokines (IL-4, IL-5, TNF-α and IFN-γ). RNA sequencing was used to uncovers genes that safranal regulate. Bone marrow-derived mast cells (BMMCs) were used to investigate the inhibitory effect and mechanism of safranal. Cytokine production (IL-6, TNF-α and LTC¬4¬¬) and NF-κB and MAPKs signaling pathway were assessed. Results: Safranal inhibited BMMC degranulation and inhibited the production of LTC4, IL-6 and TNF-α. The mechanism results showed that safranal inhibits NF-κB and MAPK pathway protein phosphorylation and decreases NF-κB p65, AP-1, 5-LO and cPLA2 nuclear translocation. In the PSA model, safranal reduced the levels of histamine and LTC4 in serum. Furthermore, in the OVA-induced asthma model, safranal reduced the level of serum IgE. The number of mast cells in lung tissue were decreased in safranal-treated mice. Safranal decreased the inflammation in lung tissue and normalized Th1/Th2 cytokine levels. Conclusions: Safranal inhibits mast cell activation and alleviates PSA and OVA-induced asthma. The possible mechanism occurs through the inhibition of the MAPK and NF-κB pathways.